Peningkatan Motivasi Dan Komitmen Kerja Pada Pegawai - Muhammad Fiqri Haikal; Nanda Dwiky Pamungkas (Pusat Riset dan Inovasi Nasional, 2024)
Companies need human resources who are educated, skilled and competent in their fields. Company management must pay attention to managing the company's human resources. The problem with employee performance in several Indonesian companies is that there is still a high level of absenteeism, this creates problems for leaders to increase employee motivation and organizational commitment to carry out work optimally. The method in this research is literature study or library search. Examine journals that are in accordance with the theory discussed, especially in the area of ​​employee motivation and commitment. All journals cited are sourced from Sinta, Google Scholar, and Garuda. The research results show that the positive influence of organizational commitment on employee performance states that motivation and organizational commitment have a significant effect on increasing employee performance.